2020
DOI: 10.3390/ma13214722
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability of Dental Reinforced CAD/CAM Hybrid Composite Blocks Compared to Regular Blocks

Abstract: This study compares the color stability of dental reinforced computer-aided design/computer-aided manufacturing (CAD/CAM) hybrid composite blocks to that of regular blocks. One hundred fifty disc-type specimens (n = 15) were prepared from five sets of hybrid composite blocks (Cerasmart-200/Cerasmart-300, KZR-CAD HR/KZR-CAD HR3, Estelite Block/ Estelite-P Block, Avencia Block/Avencia-P Block, Mazic Duro/Duro Ace). The specimen color and translucency parameter (TP) were assessed using a spectrophotometer before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…A high risk of bias could be found in all RCTs except for one [ 36 ] regarding blinding, mostly owing to the fact that blinding of participants and personnel was not applied or declared. Randomization was clearly stated in only five investigations [ 15 , 19 , 27 , 28 , 36 ]. Eleven studies reported complete information regarding sample size calculations [ 12 , 14 , 16 , 19 , 24 , 25 , 26 , 28 , 36 , 37 , 38 ], eight regarding sampling technique [ 12 , 15 , 16 , 25 , 27 , 28 , 37 , 38 ], and two regarding the comparison (control) group [ 28 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A high risk of bias could be found in all RCTs except for one [ 36 ] regarding blinding, mostly owing to the fact that blinding of participants and personnel was not applied or declared. Randomization was clearly stated in only five investigations [ 15 , 19 , 27 , 28 , 36 ]. Eleven studies reported complete information regarding sample size calculations [ 12 , 14 , 16 , 19 , 24 , 25 , 26 , 28 , 36 , 37 , 38 ], eight regarding sampling technique [ 12 , 15 , 16 , 25 , 27 , 28 , 37 , 38 ], and two regarding the comparison (control) group [ 28 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Randomization was clearly stated in only five investigations [ 15 , 19 , 27 , 28 , 36 ]. Eleven studies reported complete information regarding sample size calculations [ 12 , 14 , 16 , 19 , 24 , 25 , 26 , 28 , 36 , 37 , 38 ], eight regarding sampling technique [ 12 , 15 , 16 , 25 , 27 , 28 , 37 , 38 ], and two regarding the comparison (control) group [ 28 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bisphenol A glycol dimethacrylate (BIS-GMA) matrix is known to have a high water-absorption rate. On the other hand, absence of the hydroxyl side group in urethane dimethacrylate (UDMA) results in a less hydrophilic, more viscous matrix, which results in increased color stability of the milled material and is widely used in hybrid composite resin restorative materials [ 30 , 31 ]. The mechanism of coffee staining depends on the adsorption and sorption of the staining medium within the organic matrix of the material.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CAD/CAM has rapidly increased in recent years due to its facilitation of indirect restorations ( 6 ). New CAD/CAM materials have been introduced specifically for esthetic restorations to overcome the disadvantages associated with the use of direct resin composites ( 8 ). The ceramic and resin-based composite blocks are used with CAD/CAM technology ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%